2018
DOI: 10.7150/jca.21224
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Shikonin against Esophageal Cancer Cells and its possible mechanisms in vitro and in vivo

Abstract: Increasing evidences indicate that shikonin can suppress the tumor growth. However, the mechanisms remain elusive. In the present study, we investigated the effects and mechanisms of shikonin against esophageal cancer. The expression of hypoxia inducible factor 1α (HIF1α) and pyruvate kinase M2 (PKM2) in esophageal cancer tissues and cells was detected by immunohistochemistry and Western blot. CCK-8 was used to examine the esophageal cancer cell viability. Apoptosis and cell cycle were analyzed by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
(35 reference statements)
0
28
0
Order By: Relevance
“…The molecular mechanisms underlying the anti-cancer activity of Shikonin seemed to be complicated and may depend on the cellular context (Wang et al, 2019). So far, the reported cellular targets of Shikonin include the pyruvate kinase isoenzyme M2 (PKM2) (Chen et al, 2011;Lu et al, 2018;Tang et al, 2018b), the MAPK pathway (Mao et al, 2008;Zhao et al, 2015;Shan et al, 2017), HIF1a (Li et al, 2017;Han et al, 2018;Tang et al, 2018b), JNK (Zhai et al, 2017;Lin et al, 2018), PI3K/AKT (Zhang et al, 2015;Zhou et al, 2017;Ni et al, 2018;Tang et al, 2018b), STAT3 (Qiu et al, 2017;Tang et al, 2018a), p16INK4A and p73 (Jang et al, 2015), and PTEN (Nigorikawa et al, 2006;Chen et al, 2018;Zhang et al, 2018). These findings, at one hand, demonstrate that Shikonin can regulate various biological processes (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular mechanisms underlying the anti-cancer activity of Shikonin seemed to be complicated and may depend on the cellular context (Wang et al, 2019). So far, the reported cellular targets of Shikonin include the pyruvate kinase isoenzyme M2 (PKM2) (Chen et al, 2011;Lu et al, 2018;Tang et al, 2018b), the MAPK pathway (Mao et al, 2008;Zhao et al, 2015;Shan et al, 2017), HIF1a (Li et al, 2017;Han et al, 2018;Tang et al, 2018b), JNK (Zhai et al, 2017;Lin et al, 2018), PI3K/AKT (Zhang et al, 2015;Zhou et al, 2017;Ni et al, 2018;Tang et al, 2018b), STAT3 (Qiu et al, 2017;Tang et al, 2018a), p16INK4A and p73 (Jang et al, 2015), and PTEN (Nigorikawa et al, 2006;Chen et al, 2018;Zhang et al, 2018). These findings, at one hand, demonstrate that Shikonin can regulate various biological processes (Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin is reported to inhibit cell growth by inducing cell cycle arrest and promoting apoptosis in human NSCLC A549, gallbladder cancer NOZ and EHGB-1, esophageal cancer EC109, and epidermoid carcinoma A-431 cells [601,[603][604][605]. It can also induce necroptosis via autophagy inhibition in human NSCLC A549 cells [593], and through ROS overproduction in human nasopharyngeal carcinoma 5-8F, and glioma SHG-44, U87 and U251 cells [606,607].…”
Section: Shikoninmentioning
confidence: 99%
“…Accumulating evidence suggests that shikonin can suppress tumor growth and overcome the resistance to chemotherapy drugs in tumor cells [10]. Tang et al [11] suggested that shikonin can significantly inhibit the proliferation of esophageal cancer cells by regulating the HIF1α/PKM2 signaling pathway. Shikonin can also suppress the inflammatory immune response by…”
Section: Mediators Of Inflammationmentioning
confidence: 99%